ANALISIS MISKONSEPSI PESERTA DIDIK PADA MATERI HIDROLISIS GARAM DALAM PEMBELAJARAN DENGAN MODEL GUIDED INQUIRY (Universitas Negeri Semarang, 2021)
One of the problems in a chemistry learning is the low learning outcomes mainly due to misconception. This study aims to study the student’s misconceptions on the topic of salt hydrolysis and the possible causes that come from them. This study was a case study with a one-shot case study design. Observation sheets on learning activities, observation sheets on student’s attitude, a test pack of three-tier multiple choice model, and guidelines of interviews involving students as respondents were used in the data collection. The results of observation on the implementation of learning showed that the learning using guided inquiry model has been carried out very well, it suggested that the learning process for embedding the correct concept of salt hydrolysis material has proceeded in accordance with the steps of the guided inquiry learning model. In addition, it was observed that the students showed a very good attitude during the learning process. The student’s misconception on the topic of salt hydrolysis was in a low category with the misconception percentage of 21.7%. The student’s misconceptions observed in this study suggested that those are possible due to incomplete/false reasoning (50%), associative thinking (30%), and intuition (20%). Students' interest in the chemistry lesson was also observed to contribute to misconceptions.